The Formation of Two Hybrid Plasmids Mediated by IS26 and Tn6952 in Salmonella enterica Serotype Enteritidis - Liu, Ying-ying; He, Dan-dan; Zhang, Meng-ke; Pan, Yu-shan; Wu, Hua; Yuan, Li; Liu, Jian-hua; Hu, Gong-zheng (Frontiers in Microbiology, 2021)
To characterize the formation mechanism and characteristics of two cointegrate plasmids in Salmonella enterica serotype Enteritidis strain S13. Plasmids from strain S13 and three corresponding transconjugants were subjected to whole genome sequencing and analyzed using bioinformatics tools. The traits of two fusion plasmids in transconjugants were characterized by stability and conjugation experiments. Sequence analysis indicated that strain S13 contained four plasmids, including mcr-1-bearing pS13-1, blaCTX-M-55-carrying pS13-2, tet(M)-bearing pS13-3, and floR-carrying pS13-4. IncN1-F33:A-:B- plasmid pS13-2 respectively fused with IncFI:A-:B- plasmid pS13-3 and IncX1 plasmid pS13-4, which generated two cointegrate plasmids, designated pS13D and pS13F, which involved in two intermolecular replicative mechanisms mediated by IS26 and the novel transposon Tn6952 (TnAS3-IS26-∆ISEcp1-ramA-∆IS26- ∆TnAs1), respectively. This is the first report of the fusion of the IncN1-F33:A-:B- plasmid and IncFI:A-:B- plasmid mediated by IS26, and with IncX1 plasmid mediated by Tn6952. The formation and evolution of cointegrate plasmids could expand the resistance and host spectrum of fusion plasmids.